(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2004)
In much discussion and literature, the experience of those that fight is often ignored or left unattended in an apparent urge to diagnose or judge. This study attempted to transcend this urge and to bracket judgement and explore the experience of those who fight and who identify as fighters. The paper presents the first set of findings of this small-scale qualitative study. Further findings will be presented in the next issue of Existential Analysis.